Evaluation of safety in arch dam using post analysis including inertia force and temperature variations of water - Rahman, Alaa Jabbar; Majdi, Ali; Obied, Wissam Khlaf (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Dams considered as one if very important infrastructure, they are lifeline structures and have a vital role our economics and social life. A concrete gravity dam is one of wide used dam worldwide, it constructed from reinforced concrete and his typical cross section is triangular, the other type is arch section. A gravity dam can be combined with an arch dam into an arch-gravity dam for areas with massive amounts of water flow but less material available for a purely gravity dam. The inward compression of the dam by the water reduces the lateral (horizontal) force acting on the dam. Thus, the gravitation force required by the dam is lessened, i.e. the dam does not need to be so massive. The aim of this paper is to obtain a preliminary post analysis for an arch gravity dam by considering of typical applied loads that effects on it. In order to check and verify the dam and ensure the assumptions used during this process, the dam is analysed in different type of major effects such as own weight, water pressure, temperature and static load intertie generated from seismic load. These loads are presented in this paper in different cases, totally five cases combined between all these factors as explain in details in the section of methodology.To achieve the target of this study, modelling of an arch dam, reservoir and foundation provided by finite element using software ANSYS. An arch dam with height of 41.5 m is studied in this paper to simulate the reality of the future dam that will be erected as accurate as possible. The response of the dams is represented by the maximum displacement of it and also the stresses in each case. The results of all analysis were compared in the five cases mentioned above to determine the impact of each case as well as the worst case affecting the safety of the dam.